Regulation of WOX11 Expression Represents the Difference Between Direct and Indirect Shoot Regeneration - Liu, Jiong Hui; Dong, Wan Chen; Fei, Fang Fang; Li, Xiao Tong; Zhang, Xiao Hang; Zhou, Yangyan; Zhang, Xian Sheng; Sang, Ya Lin; Cheng, Zhi Juan (Frontiers in Plant Science, 2022)
Somatic cells of higher plants possess the remarkable ability to regenerate new individuals via reestablishing apical meristems. Reconstitution of shoot meristem is the vital process and is required for application of plant biotechnology. Under in vitro culture condition, shoot meristem can be formed directly or indirectly, depending on the absence or presence of callus as the intermediate status. However, the difference of regulatory mechanisms between the two regeneration types remains unknown. In this study, we established a bi-directional system in which shoots regenerated directly from lateral root primordia (LRP) and indirectly from hypocotyl-derived callus simultaneously. The results based on this system revealed that regulation of WOX11 expression represents the difference between the two regeneration types in two aspects. Firstly, number of founder cells expressing WOX11 is tightly associated with regeneration types. Relatively more founder cells gave rise to callus and produce larger meristem, whereas less founder cells produce LRP that regenerate smaller meristem. Secondly, non-CG DNA methylation specifically regulated WOX11 transcription in LRP and promoted direct shoot regeneration, but had no influence on indirect regeneration. The results provide new insights for understanding the regulatory mechanisms of cell fate transition during de novo organogenesis.